2018
DOI: 10.1021/acsnano.8b04106
|View full text |Cite
|
Sign up to set email alerts
|

Free-Standing Plasmonic Chiral Metamaterials with 3D Resonance Cavities

Abstract: Hollow nanocone array (HNCA) films (cm × cm), composed of two Ag and Au nanoshells, are fabricated via a low-cost and efficient colloidal lithography technique. The relative position of the Ag and Au nanoshells can be controlled to generate various chiral asymmetries. A pronounced chiroptical response is observed in the ultraviolet–visible region with the anisotropy factor up to 10–1, which is rooted in the asymmetric current oscillations and electric field distributions. Beyond previous reports on plasmonic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 58 publications
0
44
0
Order By: Relevance
“…Rajaei et al experimentally reported giant circular dichroism (CD) with ramp-shaped plasmonic nanostructures [34]. In the above-mentioned works [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], we find that all designs are based on structure-surface-confined field effects to realize a variety of applications while ignoring spatial effects such as neutral atom trapping, an application that requires a noncontact field to be implemented.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Rajaei et al experimentally reported giant circular dichroism (CD) with ramp-shaped plasmonic nanostructures [34]. In the above-mentioned works [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], we find that all designs are based on structure-surface-confined field effects to realize a variety of applications while ignoring spatial effects such as neutral atom trapping, an application that requires a noncontact field to be implemented.…”
Section: Introductionmentioning
confidence: 84%
“…Among them, there is a class of metamaterials with a special structure, named chiral metamaterials, which shows different electromagnetic response, also called chirality, to right-and left-handed circularly polarized (RCP and LCP) light [13][14][15]. This unique optical response renders chiral metamaterials highly promising candidates for a variety of applications [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In general, chiral metamaterials are designed to be single-layered (planar chiral metamaterial) because of the relative ease of their fabrication [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the deposition incident angle and azimuth angle must be precisely controlled. [ 31,39 ] In the nanotransfer printing method, nanocrescent structures are fabricated by transfer printing with oblique shadow metal deposited polydimethylsiloxane (PDMS) stamps. Their sizes are adjusted by controlling the printing pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Dry etching of metal films through a nanostructured mask is fundamentally similar to focused ion beam milling, yet it is a much faster process. With the dry etching, large areas of nanocones can be produced on planar or even non-planar surfaces [10,18,[23][24][25][26][27][28][29][30]. The third fabrication strategy is based on the self-formation of nanocones inside cylindrical nanowell templates during the deposition of the respective metal, making use of an effect which is known as aperture clogging or self-shading [15,23,31,32].…”
Section: Introductionmentioning
confidence: 99%